Multivariable control of overhead crane system by CRA method - Nundrakwang, Songmoung; Benjanarasuth, Taworn; Ngamwiwit, Jongkol; Komine, Noriyuki (My University, 2008)
In this paper, three controllers, namely I-PD, PD and I-P controllers designed by CRA method for simultaneously controlling the trolley position, load-swing angle and hoisting rope length of the overhead crane system is proposed. The non-linear model of the crane system is first approximated to be three transfer functions in accordance with the trolley position, load-swing angle and hoisting rope length respectively. Then, the corresponding parameters of the I-PD, PD and I-P controllers are designed independently based on the appropriate values of generalized time constant and characteristic ratios. The implementation results show the good performances of the overhead crane system controlled by these controllers. The speed adjustment effects and fast rejection of the disturbance effect occurred at the input force of the trolley are also shown by the experimental results. © 2008 SICE.
Keywords: CRA method; I-P; I-PD; Overhead crane system; PD